Difficult choice: angiotensin receptor antagonists - E. O. Taratukhin (Российский кардиологический журнал)
The paper is focussed on the therapeutic choice of angiotensin receptor antagonists (ARA). The author presents the data on the comparison between different sartans and their benefits which are not explained by the blood pressure reduction. The findings from large multi-centre studies (EUTOPIA, DOHSAM, and OLIVUS-Ex) are also discussed. The evidence presented justifies specific ARA choices, despite the fact that at a first glance, this medication class appears homogeneous.